Early childhood teachers’ professional learning about ICT implementation in kindergarten curriculum: A qualitative exploratory study in China - Yang, Tian; Hong, Xiumin (Frontiers in Psychology, 2022)
Many teachers have begun to adopt Information and Communication Technologies (ICT) in early childhood education (ECE) settings to support children’s learning. However, research shows that ECE teachers’ ICT implementation practice is not always appropriate, and their limited professional learning opportunities is one reason for this. Researchers worldwide have called for more understanding of professional learning that supports ECE teachers’ use of ICT in the kindergarten curriculum. In China, although ECE teachers’ ICT competencies and skills are required in national documents, little has been reported about how they are supported in learning about implementing ICT in the current curriculum. Drawing on the Technological Pedagogical Content Knowledge (TPACK) model, this study investigates how a small group of ECE teachers in China have experienced professional learning regarding ICT-related curriculum. By conducting individual interviews and analyzing public and teachers’ personal documents, this study finds that teacher participants had received diverse types of professional learning opportunities related to ICT implementation. These opportunities were provided by different organizations; however, one shared feature was a focus on the technical level of how to use ICT devices. This study also discusses the teaching-research culture underpinning participants’ professional learning. This article provides significant implications for advancing current professional learning programs.